Genes that intervene in chromosome disjunction. - Chávez Pastor, Miguel (2015)
A review of the literature provides an explanation for the chromosomal defects found in recurrent pregnancy loss in older and younger women. What seems to be apparent in these studies is that meiosis, crossing over and disjunction occur under genetic control. Studies in yeast, rats and sheep have identified numerous genes that are activated only in this period. Some of these genes have been identified in men and women but their function is still unknown.